Role of Immunotherapy in the Management of Advanced Hepatocellular Carcinoma: A Systematic Review - Addanki, Raja Narendra Divakar; Mannava, Anjali Srikanth; Ali, Mustansir Abbas; Velmurugan, Hemasri; Thangaraju, Pugazhenthan; Varshini, Talagampala Sri (Current Cancer Drug Targets, 2025)
IntroductionThe most prevalent histologic subtype of primary liver cancer, hepatocellular carcinoma, is also the third most lethal malignancy worldwide and a significant cause of cancer death. When diagnosed, it is frequently too late for curative therapies. To add to the difficulty, it is resistant to conventional systemic therapies like chemotherapy.MethodsRecently, more attention has been given to the use of immunotherapy for this condition. Immunotherapy has had a major impact on the outcome of several malignancies; several studies have revealed the potential role of immunotherapy in advanced hepatocellular carcinoma. To provide an overview of the current literature, justification, and clinical evidence for the use of immunotherapy in advanced hepatocellular carcinoma, we employed a systematic literature review (SLR) approach in this work. Additionally, we explored the benefits and rationales of various treatment combinations and described the molecular mechanisms behind resistance to a number of immunotherapy drugs.ResultsA total of 188 articles from credible journals published between 2013 and August 7, 2023, were screened. Eight of those articles were chosen for in-depth study. This systematic review concluded that the current immunotherapeutic approaches have the potential to improve outcomes for aHCC patients; however, several clinical and biological hurdles have to be overcome, and predictive markers are still eagerly needed.ConclusionTo fully realize the potential of immunotherapy agents and their combination therapies to enhance health outcomes for patients with aHCC, additional investigation and research are required.
Keywords: immunotherapy